The effect of psychological meaningfulness and perceived organisational support on the relationship between nursing workload and job satisfaction: A prospective, cross-sectional investigation. (September 2022) - Al-Hakim, Latif; Zhang, Yuping; Jin, Jingfen; Sevdalis, Nick
Abstract: Background: Evidence emphasises a strong relationship between nursing workload and job satisfaction. This study sets out to test empirically the roles of psychological meaningfulness and perceived organisational support on the nursing workload-satisfaction relationship. Objective: To investigate empirically the role and impact of psychological meaningfulness and perceived organisational support on the relationship between nursing workload and job satisfaction. Design: Prospective cross-sectional study. Setting: A large acute care and teaching hospital in China. Participants: 500 nurses were asked to participate in this study and respond to a survey questionnaire. 426 nurses participated in this study, of which 395 responses (valid response 79%, 52% general nurses, 40% nurses in charge, and 9% senior nurses) were considered valid. Methods: A multi-item questionnaire was used to assess the constructs of interest, which included demographic items; items related to nursing satisfaction, meaningfulness, and perceived organisational support; and lastly items assessing workload. Included items were a combination of previously validated scales and items co-developed between the research team and nurses of the study hospitals. Since the study relies on self-reported scales, the common latent factor technique was initially used to ensure that the common bias was not a major concern. Model fitness was tested using one-factor congeneric measurement. The research hypotheses were tested using the SPSS add-on PROCESS v3.3 model in a bootstrap approach. Results: In the first part of the analysis, 43 of 51 factors survived the initial tests using common latent factor technique and model fitness measurements. We found that the direct effect of psychological meaningfulness on the workload-satisfaction relationship was significant. This suggests that psychological meaningfulness mediates the relationship. It further illustrates that perceived organisational support acts as a moderator for the relationship and accordingly it specifies conditions under which the workload can be related to job satisfaction. However, in the presence of psychological meaningfulness, the perceived organisational support moderated the workload-psychological meaningfulness relationship and its direct effect on workload-job satisfaction relationship became non-significant. Conclusion: Our study provides an understanding of how psychological meaningfulness and perceived organisational support may play out in the context of nursing work. To the best of our knowledge, this the first study to directly measure and explore these relationships in a quantitative manner. Our results indicate the critical role of perceived organisational support, where present, in allowing nurses to see the connection between their workload and their ultimate aspirations so that their work becomes more psychologically meaningful. Tweetable abstract : This study provides an understanding of how psychological meaningfulness and perceived organisational support affect nursing work.